1992
DOI: 10.1063/1.462935
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the methyl rotation and aldehyde wagging dynamics in the S (X̃ 1A′) and T1 (ã 3A″) states of thioacetaldehyde from pyrolysis jet spectra

Abstract: Jet-cooled, laser induced phosphorescence (LIP) excitation spectra of thioacetaldehyde (CH3CHS, CH3CDS, CD3CHS, and CD3CDS) have been observed in the 15 800–17 300 cm−1 region in a continuous pyrolysis jet. The responsible electronic transition, T1 ← S0, ã 3A″← X̃ 1A′, results from an n→π* electron promotion and gives rise to a pattern of vibronic bands that can be attributed to activity of the methyl torsion and the aldehyde hydrogen out-of-plane wagging modes. Potential and kinetic energy surfaces were mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Contrary to its oxygen analog, THA is an unstable species in the gas phase (half-life of about 10 s), which polymerizes readily, usually forming cyclic trimers. The monomeric species was isolated and characterized in 1974 by photoelectron spectroscopy, followed by several other spectroscopic studies, often combined with quantum chemical calculations. THA is a C s molecule with eclipsed methyl and carbonyl groups, whose thermal stability and unimolecular reaction pathways were studied by Ding et al…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to its oxygen analog, THA is an unstable species in the gas phase (half-life of about 10 s), which polymerizes readily, usually forming cyclic trimers. The monomeric species was isolated and characterized in 1974 by photoelectron spectroscopy, followed by several other spectroscopic studies, often combined with quantum chemical calculations. THA is a C s molecule with eclipsed methyl and carbonyl groups, whose thermal stability and unimolecular reaction pathways were studied by Ding et al…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to its oxygen analog, THA is an unstable species in the gas phase (half-life of about 10 s), 35 which polymerizes readily, usually forming cyclic trimers. The monomeric species was isolated and characterized in 1974 by photoelectron spectroscopy, 35 followed by several other spectroscopic studies, [38][39][40][41][42] often combined with quantum chemical calculations. [43][44][45][46] THA is a planar (Cs) molecule with eclipsed methyl and carbonyl groups, whose thermal stability and unimolecular reaction pathways were studied by Ding et al 47 We reported previously a speculative path to TSM 48,49 based on a detailed computational study of the H-abstraction path in the oxidation of DMS by OH radicals under the hypothesis of high hydroxyl concentration.…”
Section: Introductionmentioning
confidence: 99%